(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: Medical auditing is a must to identify the short comings of healthservices provided by the health care providers and experienced by patients. Thepurpose of this study is to detect the supposing and opposing factors regardingoutdoor health services to improve the quality of outdoor health services. Materials and methods: This observational study was conducted among thepatients visiting different outdoors of Chattogram Maa-O-Shishu Hospital from Julyto December 2017 by purposive sampling technique. Total 384 respondents wereinterviewed to fill out a pretested semi structured questionnaire. The data werecollected and analyzed using the SPSS version 20. Results: Among the patients, 86.72% resided within Chattogram City Corporation.Mean age was 24.14 (±13.18) years, most (62.24%) aged from 15 and 60 years andfemales (55.46%) were predominant. Monthly income of the most (60.41%)respondents was from 11000 to 20000 taka. Specialized service was the leadingreason (40.62%) followed by cost effectiveness (33.07%) to select this hospital.Majority (47.14%) came by themselves while 38.28% were referred by the relatives.Maximum (89.58%) patients requiredless than 10 minutes time to collect ticket. Alsomost (92.19%) required less than 10 minutes time to meet doctor. In addition,60.68% of respondents availed lab facilities and 73.44% patients purchasedmedicine from hospital pharmacy. From non-buyers, unfamiliar location was themain reason in (23.18%) most patients. Treatment cost was inexpensive for 95.31%respondents. Regarding behavior, 92.19% were satisfied with doctors and 96.88%were satisfied with staffs. Almost all (98.69%) understood doctors’ advice. However,the opposing factors stated by respondents were less waiting space (5.47%), poorgeneral cleanliness (2 .605%), long queue in pharmacy (2.605%), bad toilet service(1.82%), unclean water supply (1.30%). Only 3 (0.78%) experienced misbehavior.Majority (98.69%) did not pay without receipt, but 1.04% paid to security guardwhich is not acceptable. Conclusion: By providing more emphasis on the deficiencies the service could beimproved. Certain action plan with participation of all authorized people, it wouldbe helpful to improve the quality of outdoor health services. Chatt Maa Shi Hosp Med Coll J; Vol.19 (1); January 2020; Page 47-50